STRATEGI DINAS TENAGA KERJA DALAM MENGATASI MASALAH PENGANGGURAN DI KOTA PEKANBARU - Butar Butar, Hermes Saroha; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study will analyze how the Strategy Department of Labor in Addresing Unemployment Problem in Pekanbaru City. Given the number of unemployment both from within and from outside the area to find a job in Pekanbaru city government attempted to addressing the unemplotment problem by holding exhibitions labor market in order to facilitate job seekers find work.The steps of The Department of Labor in Addressing Unemployment Problem in Pekanbaru City be very important in providing counseling or disseminination to the public or unemployed to fill job vacancies that exist both within region and outside the region. Then, the Department of Labor Pekanbaru also perform or implement workforce training in accordance with labor market demand according to the expertise or skills possessed by job seekers. The purpose of this is to determine the strategy of the Department of Labor in Addressing Unemployment Problem in Pekanbaru City and to determine the factors that influence the strategy of the Department of Labor in Addressing Unemployment Problem in Pekanbaru City. To analyze this problem the authors use the theory Tripomo which strategy is the frame or plame that integrate goals, policy and action/program organization.This research was conducted in the Department of Labor Pekanbaru city, using qualitative research methods using snowball sampling methods in the analysis of research with key informants (key informants). In collecting the data, the researcher used interview techniques, observation and documentation studies. By using key informants and informant as a supplementary source of information in addressing unemployment problem in Pekanbaru city not run well in carrying out measures to addressing unemployment. The factors that influence among others factors of infrastructure, human resources and communications.Keywords: Strategy, unemployment